Molecular typing of clinical and environmental isolates of Cryptococcus gattii species complex from southern California, United States. Issue 11 (28th August 2019) - Hurst, Steven; Lysen, Colleen; Cooksey, Gail; Vugia, Duc J.; Litvintseva, Anastasia P.; Lockhart, Shawn R.
Summary: Background: Two species complexes (SC) cause the majority of human Cryptococcus infections: Cryptococcus neoformans SC and Cryptococcus gattii SC. Infection is typically thought to be acquired following environmental exposure. In an urban setting, parks and other public spaces are a likely source of contact with C. gattii SC. Objectives: The goals of this study were to describe the genetic diversity of C. gattii SC in the California environment, to determine the extent of environmental exposure in publicly accessed areas and to correlate the genotypes of environmental C. gattii SC isolates with those from patients in southern California. Methods: Specimens from trees and soil from 13 parks and public areas of seven California counties were examined for C. gattii SC isolates. Isolates were sequence typed and compared to sequence types from human clinical isolates from the same area. Results: Multilocus sequence typing identified C. gattii sensu stricto (VGI molecular type) as well as Cryptococcus bacillisporus (VGIII molecular type). Several C. bacillisporus but none of the C. gattii sensu stricto isolates shared sequence types with human clinical isolates from southern California. Conclusions: C. gattii SC colonies exist in some California public parks. The presence of identical STs in environmental and human isolates of C. bacillisporus is suggestive of an arboreal origin of human infections. Two new tree species were documented as hosts for C. gattii SC in California, adding to the four species previously identified.